Path ahead for 'low risk' adolescents living with a Fontan circulation. Issue 7 (23rd November 2020) - Baker, David W; Dennis, Mark R; Zannino, Diana; Schilling, Chris; Moreno, Patricia D; Bullock, Andrew; Disney, Patrick; Radford, Dorothy J; Hornung, Tim; Grigg, Leeanne; d'Udekem, Yves; Ayer, Julian; et al.
Abstract : Objective: A high risk of morbidity and mortality is well documented in adults with a Fontan circulation. The difference in outcomes between those with and without significant morbidity at the time of transition to adult care has not been well characterised. Methods: We analysed clinical outcomes in patients enrolled in the Australian and New Zealand Fontan Registry ≥16 years of age. Low risk (LR) Fontan patients were defined as those without history of sustained arrhythmia, thromboembolic event, transplantation, Fontan conversion, protein-losing enteropathy, plastic bronchitis, New York Heart Association class III/IV and/or moderate/severe atrioventricular valve regurgitation or ventricular dysfunction. Increased risk (IR) patients had one or more risk factor. Results: Inclusion criteria were met in 822 patients; mean age 26±8 years, median follow-up from age 16 was 9 years, 203 had atriopulmonary connection (APC) and 619 had total cavopulmonary connection (TCPC). Survival at 30 years was higher in the LR versus IR; 94% versus 82% (p=0.005), 89% versus 77% (p=0.07) for APC and 96% versus 89% (p=0.05) for TCPC. LR patients experienced less Fontan failure (HR 0.34, 95% CI 0.23 to 0.49, p<0.001) and ventricular dysfunction (HR 0.46, 95% CI 0.29 to 0.71, p=0.001) compared with IR patients. For LR TCPC patients, modelled survival projections at 60 years were 49%–67%. Conclusions: Clinical outcomes for adolescents LR at transition to adult care are markedly superior to those who have established risk factors for Fontan failure, which is an important consideration when formulating individualised long-term risk estimates and counselling patients.